2016
DOI: 10.1094/phyto-09-15-0222-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Colletotrichum fructicola Associated to Apple Bitter Rot and Glomerella Leaf Spot in Southern Brazil and Uruguay

Abstract: Colletotrichum fructicola is the main species causing apple bitter rot (ABR) and Glomerella leaf spot (GLS) in southern Brazil, and ABR in Uruguay where GLS remains unnoticed. Thus, this work aimed to determine the genetic structure of C. fructicola isolates of both the countries. A total of 28 out of 31 Brazilian isolates (90.3%) caused typical symptoms of GLS, while only 6 of 25 Uruguayan isolates (24.0%) originating from fruits were able to infect leaves, but causing atypical symptoms. Both populations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
5
30
0
Order By: Relevance
“…The results of this and other studies ( Rockenbach et al, 2016 ; Velho et al, 2015 ) indicate that C. fructicola have an extremely aggressive behavior; within three days it causes visible symptoms on leaves inoculated with conidia or ascospores and a few days later severe defoliation. Moreover, under favorable conditions, warm temperatures and high relative humidity, abundant reproductive structures are formed on leaf lesions.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of this and other studies ( Rockenbach et al, 2016 ; Velho et al, 2015 ) indicate that C. fructicola have an extremely aggressive behavior; within three days it causes visible symptoms on leaves inoculated with conidia or ascospores and a few days later severe defoliation. Moreover, under favorable conditions, warm temperatures and high relative humidity, abundant reproductive structures are formed on leaf lesions.…”
Section: Discussionsupporting
confidence: 60%
“…However, C. karstii has not been associated with bitter rot disease in Uruguay ( Alaniz et al, 2015 ). Moreover, Uruguayan populations of C. fructicola causing bitter rot disease were found to be genetically distinct from Brazilian isolates obtained from GLS and bitter rot diseases ( Rockenbach et al, 2016 ). Therefore, new population studies are needed to compare genetic structure of C. fructicola populations causing GLS and bitter rot in Uruguay and Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…in Southern Brazil, i.e. the bitter rot (ABR) and Glomerella leaf spot (GLS) (Velho et al 2015; Rockenbach et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that some Colletotrichum isolates exhibit a particular organ specialisation being able to cause either, ABR or GLS (Velho et al 2015, 2016; Rockenbach et al 2016). Causes for such differences remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation